2022
DOI: 10.1021/acsomega.2c02708
|View full text |Cite
|
Sign up to set email alerts
|

Facile Solid-Phase Synthesis of Well-Defined Defect Lysine Dendrimers

Abstract: An efficient solid-phase method has been reported to prepare well-defined lysine defect dendrimers. Using orthogonally protected lysine residues, pure G2 to G4 lysine defect dendrimers were prepared with 48–95% yields within 13 h. Remarkably, high-purity products were collected via precipitation without further purification steps. This method was applied to prepare a pair of 4-carboxyphenylboronic acid-decorated defect dendrimers ( 16 and 17 ), which possessed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…We envison the potential of reductive cleavage for the purpose. Based on the reported method, [20] the branched peptide 17 , which possesses eight peripheral Fmoc groups, was prepared, and the subsequent reductive cleavage gave a small amount of crude product (2% yield). LCMS analysis indicated that the crude product contained 53% of the desired product 23 a with 13% and 34% of the corresponding ester ( 23 b ) and acid ( 23 c ), respectively (entry 1, Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…We envison the potential of reductive cleavage for the purpose. Based on the reported method, [20] the branched peptide 17 , which possesses eight peripheral Fmoc groups, was prepared, and the subsequent reductive cleavage gave a small amount of crude product (2% yield). LCMS analysis indicated that the crude product contained 53% of the desired product 23 a with 13% and 34% of the corresponding ester ( 23 b ) and acid ( 23 c ), respectively (entry 1, Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the proximity of dendritic branches and terminals within the dendrimer structure generates steric hindrance, which reduces reactivity and product yield while increasing side products and impurities. Finally, the introduction of building units with orthogonal protecting groups constitutes an ongoing goal of scientists aiming to offer dendrimers with structural and functionality diversity [41]. Altogether, the appropriate arrangement of protection and deprotection reactions contributes not only to improving reaction efficiency and product purity but also to the successful construction of dendrimers in general.…”
Section: Reactionsmentioning
confidence: 99%
“…Also, Liao et al prepared the "precisely defected" polylysine dendrimers using four distinctly protected lysine building units, which possess a different number and arrangement of Boc and Fmoc protecting groups on the aand u-amino groups of lysine (Fig. 7) [41]. By arranging the incorporation order of these four differently protected lysine units, polylysine dendrimers with precisely designed fracturing branches were constructed.…”
Section: Peptide Dendrimersmentioning
confidence: 99%
“…The whole scientific community continues to rely on a labor-intensive solution phase synthesis to afford glutamic acid-based dendrons, compromising yield, as depicted in Scheme 1A. 27 Unlike lysine-based dendrons, 28 glutamic acid-based dendrons NH 2 -G2-CO 2 H (Scheme 1A, where "Gn" denotes the generation) are grown on the -COOH group. 22,29 In solid phase peptide synthesis, two free COOH groups of glutamic acid can a generate six-membered cyclic anhydride when simultaneously activated using a conventional activating reagent, leading to the formation of undesired side products.…”
Section: ■ Introductionmentioning
confidence: 99%